Specificity of personal characteristics of juvenile offenders with different levels of guilt awareness - N. V. Hresa; I. V. Zhdanova; O. G. Marchenko (Bulletin of Kharkiv National University of Internal Affairs)
The results of the study on the generalisation of psychological characteristics of juvenile offenders with different levels of guilt awareness during their adaptation to the conditions of the educational colony are presented. Based on the theoretical analysis of the philosophical, psychological, scientific and legal literature and the study of legislative acts, the authors characterise guilt as a psychological formation which includes cognitive (assessment of criminal law consequences of a criminal act), behavioural (desire to confess to a crime, to condemn one's actions in front of other convicts, assessment of the likelihood of committing a crime in the future) and emotional (assessment of the attitude towards the crime, its consequences, the victim and the court verdict) components.